Trigonometry - Sullivan, Michael (London, United Kingdom : Collier Macmillan Publisher, 1988)
Textbooks in mathematics must address a variety of interests and concerns if they are to be successful tools for the teacher and student.
1. Functions and graphs -- 2. Trigonometric functions -- 3. Graphs of trigonometric functions -- 4. Analytic trigonometry -- 5. Oblique triangles and polar coordinates -- 6. Exponential and logarithmic functions -- 7. Complex numbers; vectors -- 8. Analytic geometry.
Includes index.
Keywords: TRIGONOMETRY -- CALCULUS